Pension interest at divorce : a guide to the treatment of pension interest at divorce with reference to the history, the changes made to legislation, and the expected future outcome as based upon the current outstanding issues to be addressed by the legislature and the Minister of Finance - Du Preez, Johannes Lodewicus (Stellenbosch : Stellenbosch University, 2012)
Thesis (MAcc) -- Stellenbosch University, 2010.